A pragmatic Analysis of the Interrogative Illocutionary Acts with Reference to Arabic Text of Surah As- Saffat in the Holy Qur’ān - Al-Mekhlafy, Adel Ahmed Abdullah; Al-Ghrafy, Abdusalam Mohammed Ghaleb (Arab Journal for Sciences and Research Publishing, 2023)
This study aims at investigating the illocutionary acts (pragmatic meanings) of Qur’ānic interrogations in Surah As- Saffat. In addition, it examines the correspondence level of such illocutionary acts according to Searle (1976) classifications of illocutionary acts. Since most of the Qur’ānic interrogations are not used to indicate their basic meanings, but to indicate pragmatic meanings, interpreting and analyzing such utterances may pose a problem and sometimes brings about misunderstanding, especially when they are rendered from Arabic into another language. The data of the study are 28 interrogations collected from the original Qur’ānic Arabic text of Surah As- Saffat. Qualitative content analysis has been used to examine the data by consulting well- known classical and modern Islamic books of exegesis (Tafsîr) to determine the intended pragmatic meanings of such Qur’ānic utterances. The present study proved that all the Qur’ānic interrogations in Surah As- Saffat go beyond their basic meanings to indicate different pragmatic meanings that are not said directly in the text. Those pragmatic meanings include affirmation, disaffirmation, exclamation, disdain, consulting, advice, offering, rebuke, warning, negation and threatening. Some of these illocutionary acts correspond to three types of illocutionary speech acts proposed by Searle, namely, assertives, directives and commissives. The study findings show that the illocutionary acts of such Qur’ānic interrogations are determined by their situational contexts. The study concluded that the illocutionary acts of these Qur’ānic interrogations are pragmatically rather than syntactically determined. Thus, it is strongly recommended to employ Speech Act Theory in interpreting and analyzing Qur’ānic interrogations, and other Qur’ānic speech acts.
Keywords: Illocutionary Act; Interrogations; Speech Act Theory; Surah As- Saffat